KONSEP KOREOGRAFI TARI ZAPIN PECAH TIGA PADA MASYARAKAT LABUHAN DELI - harini maelini mubarak (Gesture: Jurnal Seni Tari, 2014)
ZapinPecahTiga dance is dances from Malay tribe in Labuhan Deli. The dance have characteristic on floor pattern is triangle and figure three. Research purpose is describe about arrangement of motion Zapin Pecah Tiga dance based on concept of choreography Zapin dance, Malay dance movement, dynamics and application of floor pattern. Theory used is theory choreography, choreography on the concept of Malay dance, Zapin dance, Zapin Pecah Tiga dance, dynamics and floor pattern. Time study for two months, began early in December 2014 until February 2015. Where research in sub-district Medan Marelan. Population research is people in Labuhan Deli, artist and dancer, sample is artist and dancer  that know about Zapin Pecah Tiga dance. Data colletion technique is observation, interview, documentation and then analyzed with use qualitative descriptive method. Research result is the dances have concept Zapin dance movement is tahsyim, alif, sambar elang tahtum. And concept Malay dance movement is tandak, tari, liok. It’s have characteristic in choreography is floor pattern is triangle have meaning “tongku tiga” as a balance in life and the dances were three people. Keyword: Zapin Pecah Tiga dance